Intravenous thrombolysis guided by a telemedicine consultation system for acute ischaemic stroke patients in China: the protocol of a multicentre historically controlled study. Issue 5 (15th May 2015) - Yuan, Ziwen; Wang, Bo; Li, Feijiang; Wang, Jing; Zhi, Jin; Luo, Erping; Liu, Zhirong; Zhao, Gang
Abstract : Introduction: The rate of intravenous thrombolysis with tissue-type plasminogen activator or urokinase for stroke patients is extremely low in China. It has been demonstrated that a telestroke service may help to increase the rate of intravenous thrombolysis and improve stroke care quality in local hospitals. The aim of this study, also called the Acute Stroke Advancing Program, is to evaluate the effectiveness and safety of decision-making concerning intravenous thrombolysis via a telemedicine consultation system for acute ischaemic stroke patients in China. Methods and analysis: This is a multicentre historically controlled study with a planned enrolment of 300 participants in each of two groups. The telestroke network consists of one hub hospital and 14 spoke hospitals in underserved regions of China. The usual stroke care quality in the spoke hospitals without guidance from the hub hospital will be used as the historical control. The telemedicine consultation system is an interactive, two-way, wireless, audiovisual system accessed on portable devices. The primary outcome is the percentage of patients treated with intravenous thrombolysis within 4.5 h of stroke onset. Ethics and dissemination: The project has been approved by the Institutional Review Board of Xijing Hospital. The results will be published in scientific journals and presented to local government and relevant institutes. Trial registration number: NCT02088346 (12 March 2014).